The story of George Washington - Meadowcroft, Enid La Monte 1898-; Wilson, Edward Arthur 1886-1970. (New York Grosset & Dunlap, 1952)
A biography of the Virginia surveyor, plantation owner, and soldier who became first President of the United States.
Keywords: Washington, George -- 1732-1799.